Detecting Common Explosive Molecules Using a Wavy Monolayer Arsenene: A Density Functional Theory Study. Issue 45 (1st December 2022) - Yang, Lei; Wang, Defu; Sun, Zijian; Li, Hui; Zhu, Weihua
Abstract: A wavy arsenene endowed with a thickness of single atom was adopted to detect various common explosive molecules by density functional theory (DFT) calculations. As expected, the monolayer arsenene has a remarkable distinguishing function to these explosives due to their unique electron mediation mechanisms via van der Waals heterogeneous adsorption behavior, in terms of the variation of work function. More importantly, a novel sensitive indicator S was put forward, being helpful to sense the explosives. This finding may not only broaden the development of electronic explosion‐proof sensitive device, but also enrich basic theoretical insights. Abstract : A wavy monolayer arsenene has been adopted to detect various common explosive molecules due to its remarkable distinguishing function. This detection is based on unique electron mediation mechanisms via van der Waals heterogeneous adsorption behavior. More importantly, a novel sensitive indicator S was put forward to easily sense these explosives.